Thymidylate synthase polymorphisms and risks of human orofacial clefts. Issue 2 (13th February 2013) - Shaw, Gary M.; Yang, Wei; Perloff, Spencer; Shaw, Nathan M.; Carmichael, Suzan L.; Zhu, Huiping; Lammer, Edward J.
Abstract OBJECTIVE: Underlying mechanisms are unknown by which folic acid use in early pregnancy may reduce risks of orofacial clefts. Thymidylate synthase (TYMS) is a folate‐dependent enzyme that catalyzes reductive methylation of deoxyuridylate to thymidylate, thereby playing a central role in DNA synthesis and repair. We investigated two TYMS functional variants (a 28‐bp tandem repeat in the promoter enhancer region of the 5′‐UTR; and TYMS 1494del6 (rs16430): a 6‐bp deletion in the 3′‐UTR) for their risk of cleft palate (CP) and of cleft lip with/without CP (CLP). We investigated effect measure modification between these variants and maternal folate intake for cleft risk. DESIGN: This case‐control study included deliveries from July 1999 to June 2003 from select areas of California. Case groups included CLP or CP alone. Nonmalformed, liveborn controls were randomly selected. Maternal interviews provided information on vitamin use and dietary folate intake. DNA was derived from newborn bloodspots. RESULTS: Data were available for 304 CLP cases, 123 CP cases, and 581 controls. 1496del6 variants did not appear to influence risk of CP or CLP. Homozygosity for the 28‐bp VNTR variant influenced CP risk (odds ratios, OR = 1.8, 95% confidence interval, 1.1–3.1), particularly among Hispanic infants, OR 2.1 (1.0–4.6). Effect measure modification was observed between the 28‐bp VNTR and combined folate intake for CP with an OR of 10.0 (1.6–60.9). CONCLUSION: Although these findings are consistent with biological mechanisms, they were based on relatively small sample sizes and may represent false‐positive discoveries. Replication is warranted in other populations. Birth Defects Research (Part A) 97:95–100, 2013. © 2013 Wiley Periodicals, Inc.